Problematika Kesiapan Guru Bahasa Inggris dalam Penerapan Kurikulum Merdeka di SMAN 9 Makassar - Muhammad Ilham Dirwan; Fiah Luthfiah Bani; Putri Aulia Yuniarti (Perkumpulan Kualitama Edukatika Indonesia, 2023)
This study aims to describe the problematic picture of English teacher readiness at SMAN 9 Makassar in terms of teacher professionalism and constraints in implementing different curricula. This study uses qualitative methods through a phenomenological approach. Data collection techniques are carried out by observing, interviewing, and documenting. The results of the study show that English teachers at SMAN 9 Makassar are ready in terms of knowledge, but are not yet mentally ready to teach two different curricula, because there are several obstacles they face such as inadequate facilities, as well as the limitations of some teachers who have not received training. intensively to deal with the Independent Curriculum. In addition, the results of observing the professional competence of English teachers at SMAN 9 Makassar show that teachers have an attitude of professionalism in carrying out the Curriculum-2013 and Merdeka Curriculum.